The Influence of Therapeutic Group Therapy (TKT), Health Education and Thought Stoping (TS) on the Anxiety Level of Children’s Anxiety Levels at Menarche - Usraleli Usraleli; Erni Forwaty; Syafrisar Meri Agritubella (Poltekkes Kemenkes Riau, 2023)
Menarche is a sign of the beginning of the stage of maturity in girls. Children can experience emotional changes in the form of anxiety caused by bullying behavior when menstrual blood gets on clothes so that children feel embarrassed. This study aims to see the effect of Therapeutic Group Therapy (TKT), Health Education, Thought Stopping (TS) on school-age children's anxiety in facing menarche. This research is a quasy experiment with the Pre and Post Test approach. The number of samples in this study were 50 grade 4 students at SDN 176 Pekanbaru. Bivariate analysis using the Wilcoxon test. The results showed that most of the respondents were 11 years old (64%). The Pre-test anxiety level was in the Moderate category, there were 20 students (40%), the Post-test Anxiety Level in the Mild category, there were 36 students (72%). The results of the Bivariate Analysis obtained an anxiety level Z value of -3.5 (P-value 0.000). The application of TKT, Health Education, and TS can overcome anxiety about menarche. In conclusion, there is a decrease in the level of anxiety in facing menarche after the TKT, Health Education and TS actions.